Effect of Insurgency on Socio-Economic and Political Development of Yobe State, Nigeria - Ali, Mustapha Alhaji; Adamu, Abdullahi; Gana, Bilkisu Lawan (Kashere Journal of Management Sciences, 2024)
This article examines the effects of insurgency on the economic and political development of Yobe states of Nigeria. Indeed, one of the major issues affecting the North-Eastern states is the presence of Boko Haram insurgency, which is directly or indirectly affecting the lives, properties of the resident of the states. Boko Haram insurgency has continually posed a serious threat to the corporate existence and unity of the state. This article investigates the origin, causes, and effect of Boko Haram on socio-economic and political development of the area under study. The method used in obtaining the relevant data is the secondary source of data, in this case data were obtained from documentaries such as journals, articles, magazines, reports, newspapers, thesis and books. The study found that the activities of the insurgent groups are negatively affecting the economic and political development of the state, which has made many youth and the business men unemployed and unsheltered. To support the argument the researcher adopted Structural Violence Theory, this theory was propounded by Johan Galtung in 1969. The research recommends that the government should provide the youth and the affected business men with different skills acquisition programmes to discourage and or prevent them from redundancy; the government should in addition encourage and support religious leaders to preach peace, and tolerance in the state, to restrain the youth from all form of criminal activities. It should ensure and strictly enforce laws and order to control the activities of all citizens across the state.